2018
DOI: 10.1186/s13073-018-0568-8
|View full text |Cite
|
Sign up to set email alerts
|

Human genetic variants and age are the strongest predictors of humoral immune responses to common pathogens and vaccines

Abstract: BackgroundHumoral immune responses to infectious agents or vaccination vary substantially among individuals, and many of the factors responsible for this variability remain to be defined. Current evidence suggests that human genetic variation influences (i) serum immunoglobulin levels, (ii) seroconversion rates, and (iii) intensity of antigen-specific immune responses. Here, we evaluated the impact of intrinsic (age and sex), environmental, and genetic factors on the variability of humoral response to common p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
135
2
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 138 publications
(152 citation statements)
references
References 48 publications
14
135
2
1
Order By: Relevance
“…The variant call rate was < 97% in 11 donors, which were thus removed from this dataset. We filtered out from both datasets genetic variants based on a set of criteria detailed in [54]. These quality-control filters yielded a total of 661,332 and 87,960 variants for the HumanOmniExpress and HumanExome BeadChips, respectively.…”
Section: Human Dna Genotypingmentioning
confidence: 99%
See 1 more Smart Citation
“…The variant call rate was < 97% in 11 donors, which were thus removed from this dataset. We filtered out from both datasets genetic variants based on a set of criteria detailed in [54]. These quality-control filters yielded a total of 661,332 and 87,960 variants for the HumanOmniExpress and HumanExome BeadChips, respectively.…”
Section: Human Dna Genotypingmentioning
confidence: 99%
“…As described previously [54], we used Positional Burrows-Wheeler Transform for genotype imputation, starting with the 661,332 quality-controlled SNPs genotyped on the HumanOmniExpress array. Phasing was performed using EAGLE2 (v2.0.5) [57].…”
Section: Genotype Imputationmentioning
confidence: 99%
“…Human immune systems vary dramatically across individuals, yet the environmental and genetic determinants of this variability remain poorly characterized. Many studies have identified genetic components and environmental stimuli that alter immune cell composition in peripheral blood [1][2][3][4][5][6] . However, normal tissues and organs also consist of diverse cell types, including infiltrating immune cells.…”
Section: Introductionmentioning
confidence: 99%
“…Identifying the genetic influences on specific patterns of infiltrating immune cells is crucial to understanding disease biology. Beyond further explaining heritable manifestations of infectious diseases and autoimmunity [1][2][3][4][5][6][7][8][9] , such efforts can further uncover the drivers of characteristic immune cell signatures in the tumor microenvironment that are prognostic for cancer progression and predictive of treatment response 10 . For example, response is improved in patients with T cell-inflamed tumors compared to T cell-depleted tumors among patients receiving immune checkpoint inhibitors targeting PD1 and CTLA4 10,11 and among ovarian cancer patients receiving chemotherapy 12 .…”
Section: Introductionmentioning
confidence: 99%
“…We therefore explore the biological functions associated with the stability selected probes, to improve knowledge of the epigenetic changes that characterize differentiated immune cells. A similar two-pronged approach is used to predict other conditions and traits collected within the Milieu Intérieur study, including age, smoking, height, BMI, routine chemical and hematological laboratory tests, and the serological responses to antigens of 13 common pathogens (22). Several of these traits have not previously been modelled using all DNAm probes jointly.…”
Section: Introductionmentioning
confidence: 99%